2020
DOI: 10.1007/s00213-020-05479-y
|View full text |Cite
|
Sign up to set email alerts
|

Oxycodone self-administration and withdrawal behaviors in male and female Wistar rats

Abstract: Over the last decade oxycodone has become one of the most widely abused drugs. The emergence of oxycodone dependence as a serious health crisis has prompted a major need for animal models of oxycodone dependence with face and predictive validity. Oxycodone use in humans is more prevalent in women (Administration, 2014) and leads to pronounced hyperalgesia and irritability. However, it is unclear if the current animal model of oxycodone self-administration recapitulates these characteristics. We assessed the fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

14
40
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(58 citation statements)
references
References 77 publications
(42 reference statements)
14
40
4
Order By: Relevance
“…These findings are consistent with findings showing that women with an OUD are more motivated to obtain opioids (e.g., greater drug and sexual risk behaviors; Meade et al 2010 ), show a faster time-course to the development of an OUD (Hernandez-Avila et al 2004 ), and have higher levels of craving during abstinence as compared to men with an OUD (Back et al 2011a ; Kennedy et al 2013 ; Moran et al 2018 ; Yu et al 2007 ). They are also consistent with previous preclinical findings showing that females self-administer more heroin and oxycodone under extended access conditions than males (Carroll et al 2002 ; Towers et al 2019 ; Kimbrough et al 2020 ) and with previous findings with other drugs of abuse showing that females have higher levels of drug-seeking than males following extended access self-administration and abstinence (Lynch 2018 ). Our current findings showing that sex differences were apparent in some conditions, but not others, may also explain some discrepancies in the occurrence of sex differences under extended access conditions (e.g., Carroll et al 2002 ; Towers et al 2019 ; Kimbrough et al 2020 ; Reiner et al 2020 ; Fredriksson et al 2020 ; Venniro et al 2017 , 2019 ) since differences are likely to depend on both the training and extended access conditions.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…These findings are consistent with findings showing that women with an OUD are more motivated to obtain opioids (e.g., greater drug and sexual risk behaviors; Meade et al 2010 ), show a faster time-course to the development of an OUD (Hernandez-Avila et al 2004 ), and have higher levels of craving during abstinence as compared to men with an OUD (Back et al 2011a ; Kennedy et al 2013 ; Moran et al 2018 ; Yu et al 2007 ). They are also consistent with previous preclinical findings showing that females self-administer more heroin and oxycodone under extended access conditions than males (Carroll et al 2002 ; Towers et al 2019 ; Kimbrough et al 2020 ) and with previous findings with other drugs of abuse showing that females have higher levels of drug-seeking than males following extended access self-administration and abstinence (Lynch 2018 ). Our current findings showing that sex differences were apparent in some conditions, but not others, may also explain some discrepancies in the occurrence of sex differences under extended access conditions (e.g., Carroll et al 2002 ; Towers et al 2019 ; Kimbrough et al 2020 ; Reiner et al 2020 ; Fredriksson et al 2020 ; Venniro et al 2017 , 2019 ) since differences are likely to depend on both the training and extended access conditions.…”
Section: Discussionsupporting
confidence: 91%
“…They are also consistent with previous preclinical findings showing that females self-administer more heroin and oxycodone under extended access conditions than males (Carroll et al 2002 ; Towers et al 2019 ; Kimbrough et al 2020 ) and with previous findings with other drugs of abuse showing that females have higher levels of drug-seeking than males following extended access self-administration and abstinence (Lynch 2018 ). Our current findings showing that sex differences were apparent in some conditions, but not others, may also explain some discrepancies in the occurrence of sex differences under extended access conditions (e.g., Carroll et al 2002 ; Towers et al 2019 ; Kimbrough et al 2020 ; Reiner et al 2020 ; Fredriksson et al 2020 ; Venniro et al 2017 , 2019 ) since differences are likely to depend on both the training and extended access conditions. As with the current findings, these previous reports of sex differences in drug-seeking have typically revealed effects during extinction, but not following exposure to drug-associated cues (Lynch 2018 ).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The present results are consistent with previous opioid escalation studies in male rats (31). However, the present results are in contrast to reports of female rodents showing greater rates of opioid escalation than males (24, 32-34) in some studies, but not all (35-37). Reasons for inconsistent sex differences in rates of opioid self-administration are not presently clear and could reflect differences in either the self-administered opioid or other experimental conditions.…”
Section: Discussioncontrasting
confidence: 99%
“…Sex differences in oral (Fulenwider et al, 2020; Zanni, DeSalle, Deutsch, Barr & Eisch, 2020) and intravenous (Kimbrough et al, 2020; Nguyen, Creehan, Kerr & Taffe, 2020) oxycodone intake have been reported in rats, although another study found no sex difference in sustained IVSA of oxycodone under varying training conditions (Mavrikaki, Pravetoni, Page, Potter & Chartoff, 2017). Interestingly, even when sex differences in IVSA under fixed-ratio conditions were reported, there were no sex differences under a progressive ratio dose substitution (Nguyen, Creehan, Kerr & Taffe, 2020) or in withdrawal-induced behaviors (Kimbrough et al, 2020), suggesting similar motivation and similar induction of negative affect across sexes. Finally, Mavrikaki and colleagues have recently shown that prior to exposure to chronic morphine injections may differentially affect acquisition of oxycodone IVSA in males compared to females (Mavrikaki, Lintz, Constantino, Page & Chartoff, 2020).…”
Section: Discussionmentioning
confidence: 97%